Modulating surface plasmon resonance response by an external electromagnetic wave. (13th May 2021) - Joshi, Ashutosh; Kumar, Amrit; V, Manjuladevi; Gupta, R. K.
Abstract: We fabricated a highly sensitive layered structure of organic molecules and studied the influence of polarization of the external electromagnetic (EM) wave on the surface plasmon resonance response from the layered structure. The layered structure was formed by depositing a self-assembled monolayer (SAM) of mercaptoundecanoic acid (MUA) followed by a single layer of Langmuir-Schaefer (LS) film of traditional calamitic liquid crystal molecule, 4 -octyl-4-biphenylcarbonitrile (8CB). The SAM of MUA was found to be non-responsive towards the change in resonance angle (RA) of surface plasmon resonance (SPR) due to the change in polarization of the external EM wave. However, such layer provides a soft-surface platform for the single layer of 8CB molecules which gets perturbed locally due to the incidence of the external EM wave. We obtained an oscillatory modulation of the change in RA due to the change in polarization angle of the EM wave with respect to the plane of incidence. The magnitude of sensitivity was found to be ∼ 4 milli°/° angle of polarization of the external EM wave. This study strongly suggests that sensitivity of a SPR-based sensor can be controlled by altering the linear state of polarization of the incident external EM wave.